The Theory of the Moiré Phenomenon Volume II Aperiodic Layers - Amidror, Isaac (Computational Imaging and Vision, 2007)
Since The Theory of the Moiré Phenomenon was published it became the main reference book in its field. It provided for the first time a complete, unified and coherent theoretical approach for the explanation of the moiré phenomenon, starting from the basics of the theory, but also going in depth into more advanced research results. However, it is clear that a single book cannnot cover the full breadth of such a vast subject, and indeed, this original volume admittently concentrated on only some aspects of the moiré theory, while other interesting topics had to be left out. Perhaps the most important area that remained beyond the scope of the original book consists of the moiré effects that occur between correlated random or aperiodic structures. These moiré effects are known as Glass patterns, after Leon Glass who described them in the late 1960s. However, this branch of the moiré theory remained for many years less widely known and less understood than its periodic or repetitive counterpart: Less widely known because moiré effects between aperiodic or random structures are less frequently encountered in everyday's life, and less understood because these effects did not easily lend themselves to the same mathematical methods that so nicely explained the classical moiré effects between periodic or repetitive structures.